Potential longevity (Ki) of malting barley (Hordeum vulgare L.) grain lots relates to their degree of pre-germination assessed through different industrial quality parameters - Gualano, Nicolás Aníbal (2014)
Barley (Hordeum vulgare L.) grain germination is required to perform the malting process. Maintenance of barley seed viability during storage is crucial for the malt industry; and modern cultivars are bred for rapid grain dormancy release after physiological maturity. Low dormancy level combined with rain close to harvest induces pre-germination/pre-harvest sprouting damage. Pre-germination might not affect viability in the short term after harvest, but it could reduce potential longevity (Ki) of a barley seed lot. Ki value is inherent for each barley lot; however, its determination is time-consuming which precludes its assessment at an industrial scale. In this study we sought quantitative relationships between Ki and the pre-germination degree of barley grain lots, assessed through quality tests routinely performed by malthouses [Falling Number (FN), α-Amylase Activity and Carlsberg]. Field pre-germinated lots from one old barley cultivar (Quilmes Palomar) and artificially pre-germinated lots from major varieties currently grown in Argentina were used. Associations between Ki and values obtained from all quality tests analysed were found for Q. Palomar. However, FN was the parameter that yielded the best and simplest explanation of Ki variability. A significant positive linear Ki -FN relationship was also obtained for each modern barley cultivar.